Uwagi o karierze Rutiliusa Pudensa Crispinusa - Okoń, Danuta (Studia Europaea Gnesnensia, 2012)
The senatorial career of Rutilius Pudens Crispinus matched the turbulent history of the period. The protagonist of these deliberations began his cursus honorum in a brilliant fashion (praefectus urbi feriarum Latinarum, IIII vir viarum curandarum, quaestor urbanus, aedilis plebis Cerialis, praetor), favoured by Caracalla for his stance during the emperor’s crack-down on his brother. After the death of the princeps, during the rule of Macrinus and Heliogabalus, he was temporarily left out and demoted to less important public posts (curator Fanestrium Pisaurensium, curator viarum Clodiae Cassiae et Ciminiae, iuridicus Aemiliae Etruriae Liguriae). He returned to grace during the reign of Alexander Severus, thanks to the latter’s policy of drawing on the solutions of the first Severs. Crispinus obtained command of a legion (legatus legionis XV Apollinaris), 4 governorships (legatus Augusti pro praetore provinciae Lusitaniae, legatus Augusti pro praetore Thraciae, legatus Augusti pro praetore Syriae Phoenices, proconsul provinciae Achaiae) and a consulate. Under Maximinus the Thracian he commanded the defence of Aquileia. The next emperor, Gordian III granted him important and honourable offices (legatus Augusti pro praetore provinciae Hispaniae citerioris et Callaeciae, curator Teanensium, Interamnatium, Venafranorum, Aquinatium, legatus Augusti pro praetore ad census acceptandos provinciae Lugdunensis et provinciae Hispaniae Baeticae). Crispinus died in a period when his career was gathering pace again , and more promotions seemed in store for him in the near future.